Phytometabolomic analysis of boiled rhizome of Nymphaea nouchali (Burm. f.) using UPLC-Q-TOF-MSE, LC-QqQ-MS & GC–MS and evaluation of antihyperglycemic and antioxidant activities. (16th April 2021) - Anand, Ajay; Komati, Anusha; Katragunta, Kumar; Shaik, Hussain; Nagendla, Narendra Kumar; Kuncha, Madhusudana; Mudiam, Mohana Krishna Reddy; Babu, Katragadda Suresh; Tiwari, Ashok Kumar
Highlights: Phytometabolomic analysis of N. nouchali boiled rhizome was performed. N. nouchali boiled rhizome powder displayed antihyperglycemic activity. Displayed antioxidant activity, prevented hemoglobin and insulin glycation. Oxidative stress induced mitochondrial membrane potential disturbances were assuaged. Abstract: Phytometabolomic analysis of Nymphaea nouchali (Burm. F.) boiled rhizome was carried out utilizing UPLC-Q-TOF-MS E, LC-QqQ-MS and GC–MS techniques and evaluated for antihyperglycemic and antioxidative stress potentials. Metabolomic analysis revealed presence of multiple antidiabetic and antioxidant compounds. Boiled rhizome powder exhibited potent antihyperglycemic activity against sugar-induced postprandial hyperglycemia in rats plausibly due to the presence of intestinal α-glucosidase inhibitory and augmenting cellular glucose uptake activities. It also prevented hyperglycemia-induced hemoglobin and insulin glycation. Rhizome displayed potent reducing power, effectively scavenged various reactive oxygen species. It displayed antioxidative stress potential in assuaging H2 O2 induced erythrocyte hemolysis and antioxidant activity by inhibiting membrane lipid peroxidation. Boiled rhizome was also found to preserve the loss of cellular antioxidants under H2 O2 induced oxidative stress and disturbances caused to mitochondrial membrane potential. This is the first research reporting boiled N. nouchali rhizome as an ideal food material to manage the cause of hyperglycemia and resultant oxidative stress.